The assembly of the land (zemskii sobor): historiographies and mythologies of a Russian “parliament”1 - Sablin, Ivan; Kukushkin, Kuzma V. (Planting parliaments in Eurasia, 1850-1950, 2021)
Focusing on the term zemskii sobor, this study explored the historiographies of the early modern Russian assemblies, which the term denoted, as well as the autocratic and democratic mythologies connected to it. Historians have debated whether the individual assemblies in the sixteenth and seventeenth century could be seen as a coherent institution, what constituencies were represented there, what role they played in the relations of the Tsar with his subjects, and if they were similar to the early modern assemblies elsewhere. The growing historiographic consensus does not see the early modern Russian assemblies as a coherent institution. In the nineteenth-early twentieth century, history writing and myth-making integrated the zemskii sobor into the argumentations of both the opponents and the proponents of parliamentarism in Russia. The autocratic mythology, advanced by the Slavophiles in the second half of the nineteenth century, proved more coherent yet did not achieve the recognition from the Tsars. The democratic mythology was more heterogeneous and, despite occasionally fading to the background of the debates, developed for some hundred years between the 1820s and the 1920s. Initially, the autocratic approach to the zemskii sobor was idealistic, but it became more practical at the summit of its popularity during the Revolution of 1905-1907, when the zemskii sobor was discussed by the government as a way to avoid bigger concessions. Regionalist approaches to Russia’s past and future became formative for the democratic mythology of the zemskii sobor, which persisted as part of the romantic nationalist imagery well into the Civil War of 1918-1922. The zemskii sobor came to represent a Russian constituent assembly, destined to mend the post-imperial crisis. The two mythologies converged in the Priamur Zemskii Sobor, which assembled in Vladivostok in 1922 and became the first assembly to include the term into its official name.
Im Zusatz zum Titel ist "1" hochgestellt
Gesehen am 28.06.2021